Interactive affordance design strategy for nutrition labels of prepackaged foods - TAN Yuan-yuan; JIANG Peng-ru (Shipin yu jixie)
Objective: To explore the theoretical relationship between interactive availability thinking in the design of nutrition labels for prepackaged foods； To improve consumer awareness and trust, guide consumers' healthy choice behavior, and construct a design framework for prepackaged food labels based on interactive availability model. Methods: Based on the two-tier result model of interactive availability and the empirical evidence of knowledge, this paper analyzes how the design can help the nutrition labels of prepackaged food to effectively convey information and improve the labels' value and its guidance role. Results: Four interactive design strategies were proposed: enhancing the influence of unconscious interaction intention between consumers and food nutrition labels, improving the information awareness of consumers and food nutrition labels through multiple channels, constructing the unconscious public concept mechanism between consumers and food nutrition labels, and constructing the interaction mode of consumer value cognition. Conclusion: Interactive availability is helpful to explore how to improve the practical value of nutrition labeling of prepackaged foods under the interdependence of consumers and prepackaged food nutrition labels, and achieve the expectation of guiding the healthy dietary habit of consumers via nutrition labels.